2017
DOI: 10.1161/atvbaha.117.310051
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of In-Stent Restenosis by Cholesteryl Ester Transfer Protein Inhibition

Abstract: Inhibiting cholesteryl ester transfer protein activity in New Zealand White rabbits with iliac artery balloon injury and stent deployment increases HDL levels, inhibits vascular smooth muscle cell proliferation, and reduces neointimal hyperplasia in an scavenger receptor-B1, PDZ domain-containing protein 1- and phosphatidylinositol-3-kinase/Akt-dependent manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…Further, In the DEFINE study with anacetrapib, there were no significant changes in C-reactive protein levels [120]. The potential significance of a focal anti-inflammatory activity of anacetrapib is supported by the very recently described reduction of in-stent restenosis in rabbits treated with the analog des-fluoro anacetrapib [121], also confirming prior data showing reduced intimal hyperplasia and functional endothelial regeneration with this agent [121].…”
supporting
confidence: 77%
“…Further, In the DEFINE study with anacetrapib, there were no significant changes in C-reactive protein levels [120]. The potential significance of a focal anti-inflammatory activity of anacetrapib is supported by the very recently described reduction of in-stent restenosis in rabbits treated with the analog des-fluoro anacetrapib [121], also confirming prior data showing reduced intimal hyperplasia and functional endothelial regeneration with this agent [121].…”
supporting
confidence: 77%
“…43,44 A recent study showed that increasing HDL via CETP inhibition inhibited neointimal hyperplasia in ballooninjured rabbits, that the benefit was attributed to the antiinflammatory properties of HDL. 45 In fact, it has previously been demonstrated that low HDL-C in healthy subjects was associated with an increased inflammatory response to an LPS challenge, 21 further supporting the anti-inflammatory role of endogenous HDL. It is thus tempting to speculate that CETP-expressing species have increased flexibility to respond to invading Gram-negative organisms that release endotoxin/ LPS.…”
Section: Discussionmentioning
confidence: 89%
“…Upon LPS administration, reduced plasma CETP concentration results in increased HDL, which has well‐documented anti‐inflammatory properties . A recent study showed that increasing HDL via CETP inhibition inhibited neointimal hyperplasia in balloon‐injured rabbits, that the benefit was attributed to the anti‐inflammatory properties of HDL . In fact, it has previously been demonstrated that low HDL‐C in healthy subjects was associated with an increased inflammatory response to an LPS challenge, further supporting the anti‐inflammatory role of endogenous HDL.…”
Section: Discussionmentioning
confidence: 91%
“…47 Consistently, a recent study published in ATVB used a new rabbit CETP knockout model to demonstrate that CETP-deficiency results in elevated HDL-C levels, increased cholesterol efflux capacity of apoB-depleted plasma, markedly reduced levels of VLDL, and protection against cholesterol diet-induced atherosclerosis. 48 Another study found that pharmacological inhibition of CETP activity reduces in-stent restenosis via inhibition of vascular smooth muscle cell proliferation, 49 suggesting that CETP inhibition may be a potential strategy to protect against ASCVD and related vascular damage. Whereas these animal models show beneficial effects of loss of CETP, human studies are less conclusive.…”
Section: High-density Lipoproteinmentioning
confidence: 99%